Culprit vessel vs. immediate multivessel vs. out-of-hospital staged intervention for patients with non-ST-segment elevation myocardial infarction and multivessel disease - Wang, Chen; Lang, Jiachun; Zhang, Jingxia; Hu, Yuecheng; Han, Chuyi; Xu, Rongdi; Wu, Jikun; Liu, Chunwei; Li, Wenyu; Li, Tingting; Wei, Ao; Qi, Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and aims The optimal interventional strategy remains undetermined in hemodynamically stable patients with NSTEMI and MVD. This study aimed to examine clinical prognosis among culprit vessel, immediate multivessel, and staged percutaneous coronary intervention (PCI) in patients with NSTEMI and MVD. Methods This retrospective, observational, single-center study included 943 hemodynamically stable patients with NSTEMI and MVD who had undergone successful drug-eluting stent (DES) implantation from January 2014 to December 2019. Patients were categorized into culprit lesion-only PCI (CL-PCI), immediate multivessel PCI (MV-PCI), and out-of-hospital staged MV-PCI according to PCI strategy. The primary outcome was the composite of major adverse cardiac events (MACEs), including all-cause death, myocardial infarction (MI), or unplanned repeat revascularization. The secondary outcomes were all-cause death, cardiac death, MI, and unplanned repeat revascularization. Results Over a median follow-up of 59 months, immediate MV-PCI was associated with a lower risk of all-cause death than CL-PCI (HR: 0.591, 95%CI: 0.364–0.960, P = 0.034). Out-of-hospital staged MV-PCI was associated with a reduced risk of MACE (HR: 0.448, 95%CI: 0.314–0.638, P < 0.001) and all-cause death (HR: 0.326, 95%CI: 0.183–0.584, P < 0.001) compared with CL-PCI. The above results were accordant after multivariate COX analysis and propensity score matching. MACE (HR: 0.560, 95%CI: 0.385–0.813, P = 0.002) and repeat revascularization (HR: 0.627, 95%CI: 0.400–0.982, P = 0.041) were significantly less likely to occur with out-of-hospital MV-PCI rather than immediate MV-PCI. However, the incidences of primary and secondary outcomes were comparable between immediate and staged PCI after confounder adjustment using multivariate regression and propensity score matching analysis. For subgroup analyses stratified by synergy between PCI with taxus and cardiac surgery score, staged MV-PCI was found to lower the risk of MACE compared with immediate MV-PCI in patients with more complex coronary disease. Conclusion Hemodynamically stable patients with NSTEMI and MVD benefited from the strategy of MV-PCI. Patients with complex coronary anatomy treated with out-of-hospital staged MV-PCI rather than immediate MV-PCI had lower risks of MACE. These need to be confirmed in the future randomized study.